ADMINISTRATION OF NASYA IN PAEDIATRIC AGE GROUP – A BIRD’S EYE VIEW - GUPTA, DR.NEERAJ KUMAR (International Journal of Psychosocial Rehabilitation, 2020)
Shodhana chikitsa (detoxification therapy) includes panchakarma which is the ultimate mind body healing experience for detoxifying the body, strengthening the immune system, restoring balance and wellbeing. It is one of the most effective healing modality in ayurvedic treatment. Childhood is very crucial period where child pick up growth and development with respect to physical, physiological and social aspect. Bala is less tolerable as he has aparipakva dhatu (Immature tissue elements). With delicate body, unable to express their feeling and predominance of sleshma dhatu they are more vulnerable to disease. To deal with this problem a need for a radical approach is required in the modern times. But the classical texts consider bala as Ayogya for panchakarma therapies. Hence a small effort is taken to highlight on the effect of Nasya in Paediatric age group.